In and Around Music Theory and the Academy: A Perspective - Horace J. Maxile, Jr. (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
This article is part of a special forum titled “Ethnic Diversity in Music Theory: Voices from the Field.” In a narrative style, it presents the perspective of a mid-career music theorist who identifies himself as African American. While this perspective uses personal anecdotes, childhood memories, and a little humor to frame the narrative, issues of diversity, marginality, and race are at the center of the discussion. Also presented are directed calls for the Society for Music Theory to make even greater strides toward engaging teachers and students from HBCUs (Historically Black Colleges and Universities) and other institutions that primarily serve people of color. Such engagements would diversify the ranks of our membership and graduate student populations, as ethnically diverse perspectives might compliment our historical, analytical, and critical discourses.